ANALISIS KINERJA KEUANGAN PADA PT. ASKRINDO - Aritonang, Angel Yolanda Patricia; Ndruru, Agustinus; Lumban Gaol, Jonner; Silaen, Novia Ruth (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2023)
This study aims to analyze the financial performance at PT. Askrindo with a focus on liquidity and solvency ratios. Insurance companies have an important role in providing services to overcome risks that occur in the future. The performance of these financial companies is evaluated using financial statements consisting of a balance sheet and profit and loss. The ratio of liquidity and solvency was chosen as the main analysis tool in this study. The results of the analysis show that PT. Askrindo has good liquidity performance, where current assets can adequately cover current liabilities. The liquidity ratio during the period 2019 to 2022 shows a positive increase reaching an average of 297% in 2022. However, there has been a decline in the solvency ratio, especially in the debt to equity ratio, which has decreased and averaged 1.05% in 2019 to 0.78 % in 2022. This situation can affect the company's ability to bear high risks, especially due to high premiums. Therefore, PT. Askrindo needs to take steps to raise capital and ensure the efficient use of assets to strengthen its overall financial position. In conclusion, even though PT Askrindo has good liquidity performance, the company must increase capital and improve its solvency ratio. This is expected to increase the confidence of creditors and investors and strengthen the company's ability to face risks in the future